Analysis of the Influence of the MBKM Program in Teaching Field - Kasih, Julianti; Djajalaksana, Yenni M.; Zakaria, Teddy Markus; Edi, Doro (Interdisciplinary Social Studies, 2022)
Background: The field of education is one of the industries most affected by the COVID-19 Pandemic, namely the move from face-to-face learning to online learning. At the same time, the Indonesian Minister of Education encouraged the Merdeka Belajar Kampus Merdeka program where one of its programs is the Teaching Campus. The involvement of students of the Faculty of Information Technology in online teaching digital marketing at high schools in Bandung is a form of implementation of the teaching campus program. There is a problem because students do not have experience, so it is questionable whether online teaching that limits the teacher's interaction with students can have a positive impact. Aim: The study was conducted with the aim of seeing how much impact student online teaching has on students. Method: The research was conducted through a survey, using AMOS 28 for quantitative analysis. The questionnaire tool is submitted through a Google Form and distributed electronically via Whatsapp and Google Classroom. Findings: Significant results were obtained on the relationship of teaching variables and Student variables. with a total influence of .194. It is proven that a positive impact is obtained.